Design of Load Balancing Using Static Route Address List Method In The Case Study of Tambakrejo Village Tulungagung - Vico Indira Purnomo (NAROTAMA UNIVERSITY, 2022)
internet plays a very important role today, both to search for information and knowledge. In the development of internet networks, many factors influence it, such as the geographical location of the area, supporting facilities such as signal towers, construction costs, and Internet Service Providers (ISP) that cover the area. The purpose of this study is to build an internet network in Tambakrejo village, which has very difficult internet access due to its geographical location which is very far from urban areas and very few supporting facilities in the construction of internet networks, so the authors develop a solution using devices such as the Router Router, hubs, dongle modems, and bolic e-goen pans, and uses a load balancing method to stabilize the activity load of all connected devices. the final result expected by the authors in this study is so that people who live in the Tambakrejo village of Tulungagung city can feel internet access that is easier and more stable, and the construction of their internet network does not cost much.